2008
DOI: 10.1186/1475-2840-7-11
|View full text |Cite
|
Sign up to set email alerts
|

Diabetic retinopathy is associated with pulse wave velocity, not with the augmentation index of pulse waveform

Abstract: Background: To investigate the clinical differences between pulse wave velocity and augmentation index in diabetic retinopathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(39 citation statements)
references
References 24 publications
2
32
0
5
Order By: Relevance
“…The automatic pulse wave analyzer (Omron Colin, Tokyo, Japan) was recruited to measure baPWV and ABI, as described previously [8]. Briefly, patients were guided into the supine position on a bed and allowed to rest for at least 5 min before examination.…”
Section: Assessment Of Arterial Stiffnessmentioning
confidence: 99%
“…The automatic pulse wave analyzer (Omron Colin, Tokyo, Japan) was recruited to measure baPWV and ABI, as described previously [8]. Briefly, patients were guided into the supine position on a bed and allowed to rest for at least 5 min before examination.…”
Section: Assessment Of Arterial Stiffnessmentioning
confidence: 99%
“…On the other hand, association between AIx and diabetic retinopathy was not statistically significant. The clinical significance appears to be different between PWV and AIx in patients with diabetes 52 . PWV might be a marker of vascular injury caused by chronic hyperglycaemia, rather than a marker of retinopathy 51 .…”
Section: Microvascular Complicationsmentioning
confidence: 99%
“…Recently, Cardoso et al demonstrated that increased central arterial stiffness measured by pulse wave velocity (PWV) is associated with the presence of microvascular complications (retinopathy and peripheral neuropathy) independently of other established determinants of aortic stiffness [21]. There was a significant positive association between the presence of diabetic retinopathy and PWV, but not with the AI of pulse waveform among Japanese type 2 diabetic patients without macroangiopathy [22]. The results of studies on type 2 diabetic patients cannot be extrapolated directly to type 1 diabetes.…”
Section: Discussionmentioning
confidence: 99%